Evaluation of Approaches to Technique in the Context of War and Military Profession - Niyazi Kayahan Boyacı (İstanbul Üniversitesi Sosyoloji Dergisi)
This study aims to discuss various approaches to technique using technical and political philosophy concepts, and to evaluate these approaches concerning war and the military profession. It is argued that establishing a strategy with the appropriate political goals and war tools cannot be established without first asking how and by whom technique is used, and how the worlds created by technique make the subject dependent on technique. The “pharmakon” metaphor was used to suggest that the objects humans create and bring into being can change pre-existing social relations and that any technique can have beneficial and destructive effects. The transformation of transhumanism, which re-discusses what it means to be human through technological creation, into an ideology that legitimizes domination through technique has been criticized. Moreover, the goals of current wars have been assessed in this context. Aside from the fact that each new technique changes the character of war, it has been attempted to convey that new techniques such as automation and artificial intelligence make the fighting subject dependent on itself and endanger its subjectivity by associating it with political decision-makers and the military profession.